Laryngeal effects of stimulation of rostral and ventral pons in the anaesthetized rat - Lara-Muñoz, José Pablo; Dawid-Milner, Marc Stefan; López-González, Manuel Víctor; Montes, Carmen; Spyer, KM; González-Barón, Salvador (Elsevier, 2002)
In order to study the importance of two pontine regions modulating laryngeal resistance, electrical current or microinjections of glutamate (10–30 nl, 1–3 nmol) were made into the pontine parabrachial complex and the A5 region in spontaneously breathing anaesthetized rats. Two distinct patterns of laryngeal and respiratory responses were elicited. An increase of subglottal pressure was accompanied with an expiratory facilitatory response consisted of a decrease in both respiratory rate and phrenic nerve activity. A decrease of subglottal pressure was accompanied with an inspiratory facilitatory response consisted of an increase in both respiratory rate and phrenic nerve activity. The modification of laryngeal calibre occurred during both respiratory phases in most cases. The concomitant cardiovascular changes of these responses were also analyzed. Controls using guanethidine to block autonomic responses which might interact with respiratory control were also made. Histological analysis of stimulation sites showed a topographical organization of these responses: laryngeal constriction was evoked from Kölliker–Fuse, medial parabrachial nuclei and A5 region, whilst the laryngeal dilation was evoked from the lateral parabrachial nucleus.
Keywords: Respiración - Regulación - Modelos animales; Laringe - Modelos animales; Experimentación animal; Respiratory and laryngeal regulation; Pons; Parabrachial complex; A5 Region; Glutamate; Rat